Analysis of cracking potential and micro-elongation of linerboard - Panthai, Supattra; Patchiyo, Tongchai; Puthson, Pratuang; Somboon, Phichit (Agriculture and Natural Resources, 2016)
Folding cracks of linerboards in relation to their micro-elongation and the forming conditions were studied using an industrial linerboard machine with a top former. The experiments consisted of the study of various forming conditions by manipulating the jet/wire speed ratio to produce linerboard with differences in fiber structures that were related to the cracked and uncracked products. The results showed that changes to the jet/wire speed ratio of about 0.01-0.02 to improve the tested folding endurance in the machine direction potentially produced folding cracks in the linerboard, which indicated an ambiguous interpretation of the foldability tests. The delaminated cracked layers were found to have a high folding endurance and tensile strength, while the decrease in the micro-elongation formulated in this study was found to be related to cracking. A lower micro-elongation of about 350-500 um/N.g was found in a range of products with folding cracks.